Analisis Pemanfaatan Qris dalam Kemudahan Pembayaran Konsumen Car Free Day Kraksaan - Rukayyah; Tri Wisudaningsih, Endah; Aqidah, Waqiatul (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to explore the use of Quice Response Code Indonesia Standard (QRIS) in payment transaction at Car Free Day (CFD) Kraksaan and its impact on Micro, Small and Medium Enterprises (MSMEs). Qualitive research methods were used with a descriptive approach through interviews with Kraksaan CFD traders and visitors who use Qris. The interview results show that QRIS is used by traders to simplify the payment process, imcrease transaction efficiency, and reduce the problem of returns, the use of QRIS is also considered to provide additional security in transactions. Even thought there are several problems related to consumer balaces, the use of QRIS is considered to be optimal. Merchants who have not yet used QRIS are expected to immediately adopt it to expand the reach of payments and increase transaction efficiency. In conclusion, the use of QRIS has a positive impact in increasing the efficiency and security of transactions in CFD Kraksaan, and is expected to provide greater benefits and society as a whole.